Well-being in dementia: a cross-sectional dyadic study of the impact of multiple dimensions of strain on persons living with dementia and their family care partners. (6th February 2019) - Miller, Lyndsey M.; Kaye, Jeffrey A.; Lyons, Karen S.; Lee, Christopher S.; Whitlatch, Carol J.; Caserta, Michael S.
ABSTRACT: Background and Purpose: The impact of dementia-related stressors and strains have been examined for their potential to threaten the well-being of either the person with dementia or the family care partner, but rarely have studies considered the dyadic nature of well-being in dementia. The purpose of this study was to examine the dyadic effects of multiple dimensions of strain on the well-being of dementia care dyads. Methods: Using multilevel modeling to account for the inter-relatedness of individual well-being within dementia care dyads, we examined cross-sectional responses collected from 42 dyads comprised of a hospitalized patient diagnosed with a primary progressive dementia (PWD) and their family care partner (CP). Both PWDs and CPs self-reported on their own well-being using measures of quality of life (QOL-Alzheimer's Disease scale) and depressive symptoms (Center for Epidemiological Studies Depression Scale). Results: In adjusted models, the PWD's well-being (higher QOL and lower depressive symptoms) was associated with significantly less strain in the dyad's relationship. The CP's well-being was associated with significantly less care-related strain and (for QOL scale) less relationship strain. Conclusions: Understanding the impact of dementia on the well-being of PWDs or CPs may require an assessment of both members of the dementia care dyad in order to gain a complete picture of how dementia-related stressors and strains impact individual well-being. These results underscore the need to assess and manage dementia-related strain as a multi-dimensional construct that may include strain related to the progression of the disease, strain from providing care, and strain on the dyad's relationship quality.